2023
DOI: 10.1186/s13045-023-01518-1
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing immunotherapy for brain metastases: insights into tumor–brain microenvironment interactions and emerging treatment modalities

Dairan Zhou,
Zhenyu Gong,
Dejun Wu
et al.

Abstract: Brain metastases signify a deleterious milestone in the progression of several advanced cancers, predominantly originating from lung, breast and melanoma malignancies, with a median survival timeframe nearing six months. Existing therapeutic regimens yield suboptimal outcomes; however, burgeoning insights into the tumor microenvironment, particularly the immunosuppressive milieu engendered by tumor–brain interplay, posit immunotherapy as a promising avenue for ameliorating brain metastases. In this review, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 227 publications
0
4
0
Order By: Relevance
“…Melanoma accounts for the third prevalent cause of brain metastasis and the progression to brain metastasis leads to poor prognosis 38 . Activated T cells can migrate to the brain and induce antitumor responses 39 , 40 , providing a potential strategy for inhibiting brain tumors. Following the same post-operative adjuvant procedures of the primary model of melanoma, a secondary tumor was inoculated by intracranial injection of luciferase-expressing B16-F10 cells (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma accounts for the third prevalent cause of brain metastasis and the progression to brain metastasis leads to poor prognosis 38 . Activated T cells can migrate to the brain and induce antitumor responses 39 , 40 , providing a potential strategy for inhibiting brain tumors. Following the same post-operative adjuvant procedures of the primary model of melanoma, a secondary tumor was inoculated by intracranial injection of luciferase-expressing B16-F10 cells (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…These factors collectively contribute to impeding the effectiveness of CAR T-cells in CNS tumors. [47][48][49] By utilizing repetitive in vivo TPLSM we are capable of elucidating intratumoral CAR T-cell dynamics from early stages of tumor formation until late timepoints, when large tumors have formed. After intracerebral injection of CAR T-cells, we initially observed higher intratumoral densities of EpCAM-directed CAR T-cells compared to undirected CAR T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have also shown the benefit of pembrolizumab administration in these patients ( 19 , 20 ). Pembrolizumab has demonstrated efficacy in treating a variety of cancer types, including melanoma and non-small cell lung cancer, and there have been promising results in patients with brain metastases ( 19 , 21 ). In addition, ongoing research is focused on exploring ways to improve the response of brain metastases to ICIs, such as combining treatment with other therapies or optimizing dosing regimens ( 19 , 22 ).…”
Section: Discussionmentioning
confidence: 99%